Land suitability evaluation for grass jelly (Mesona palustris BI.) and land conservation in Nawangan, Pacitan Regency - Dika Dwi Darmawan; M Mujiyono; Joko Winarno; S Supriyadi (Brawijaya University, 2019)
One of land degradation problems in Nawangan is surface erosion, throughout the years it widespread. Land conservation by planting plantations in the potential disturbed area is one way to solve this problem. Grass jelly or locally known as janggelan (Mesona palustris BI.) can be an alternative for this land conservation, Nawangan has suitable geographic location and grass jelly cultivation is profitable for the surroundings economically. Aim of this study was to evaluate land suitability for grass jelly to solve the land degradation problem in Nawangan. Purposive sampling methods were used to determine sample point, then soil sample analyzed in a laboratory, and overlay of type of soil map and land use map. After soil characteristic was obtained, then the matching process was used. Finally, from this study showed that land suitability classes in Nawangan for grass jelly are very suitable on (S1) land unit LaS and LaK, suitable (S2) on land unit Lil, LiH, LiS and LaH, and marginal suitable (S3) on land unit LaL and LiK.